BMX race-start dynamics: Coupling on-track measurements and physics-based modelling for performance optimisation - Fortier, A.; Violain, M.; Brunet, E.; Clanet, C. (Journal of Science and Cycling, 2025)
A fast and stable launch is decisive in Bicycle Moto-Cross (BMX) racing, yet the underlying interplay between rider power production, bicycle gearing and ramp geometry has received little attention in the engineering literature. Using high-frequency field measurements gathered on the Olympic track of Saint Quentin-en-Yvelines (France), we develop and validate a physics-based model that predicts the rider`s velocity profile over the start ramp. The formulation combines (i) a Hill-type linear torque-cadence relationship fitted to instrumented-crank data, (ii) an energy balance that accounts for aerodynamic and rolling losses, and (iii) the measured track slope. Model predictions agree with experiments for three gear ratios. We then explore two practical optimisation criteria—minimum time to the first bump and maximum mean acceleration on the ramp—to identify gearing strategies tailored to individual athletes. The framework illustrates how on-track sensing can be translated into actionable engineering guidelines for coaches and riders.